Autosomal recessive variations of TBX6, from congenital scoliosis to spondylocostal dysostosis. Issue 6 (22nd February 2017) - Lefebvre, M.; Duffourd, Y.; Jouan, T.; Poe, C.; Jean‐Marçais, N.; Verloes, A.; St‐Onge, J.; Riviere, J.‐B.; Petit, F.; Pierquin, G.; Demeer, B.; Callier, P.; et al.
Abstract : Proximal 16p11.2 microdeletions are recurrent microdeletions with an overall prevalence of 0.03%. In patients with segmentation defects of the vertebra (SDV), a burden of this microdeletion was observed with TBX6 as a candidate gene for SDV. In a published cohort of patients with congenital scoliosis (CS), TBX6 haploinsufficiency was compound heterozygous with a common haplotype. Besides, a single three‐generation family with spondylocostal dysostosis (SCD) was reported with a heterozygous stop‐loss of TBX6 . These observations questioned both on the inheritance mode and on the variable expressivity associated with TBX6 ‐associated SDV. Based on a national recruitment of 56 patients with SDV, we describe four patients with variable SDV ranging from CS to SCD associated with biallelic variations of TBX6 . Two patients with CS were carrying a proximal 16p11.2 microdeletion associated with the previously reported haplotype. One patient with extensive SDV was carrying a proximal 16p11.2 microdeletion associated with a TBX6 rare missense change. One patient with a clinical diagnosis of SCD was compound heterozygous for two TBX6 rare missense changes. The three rare variants were affecting the chromatin‐binding domain. Our data illustrate the variable expressivity of recessive TBX6 ranging from CS to SCD. Abstract :